How Escaping the Middle-Income Trap: Key Factors for Indonesia's Growth? - Feny Marissa; Abdul Bashir; Alghifari Mahdi Igamo; Dwi Darma Puspita Sari; Deassy Apriani; Ichsan Hamidi (Jurnal Ekonomi Pembangunan)
This study investigates the complex interplay between human development index, foreign direct investment, and investment efficiency in driving economic growth. Utilized time-series data during 2000 to 2022, sourced from the World Bank and the Asian Development Bank. Employing the ARDL model. The findings reveal a strong positive correlation between HDI and economic growth, highlighting the critical role of investments in education, health, and social welfare. While FDI significantly contributes to economic growth through technology transfer and productivity enhancement, the study surprisingly finds limited evidence of a direct link between investment efficiency and economic growth. This suggests that factors such as institutional quality and innovation play a more dominant role. These findings have crucial implications for Indonesia, which faces the challenge of escaping the middle-income trap. Prioritizing human development, attracting high-quality FDI, and fostering a conducive investment climate through institutional reforms are crucial for sustainable and inclusive growth. By investing in human capital, promoting technological innovation, and effectively leveraging FDI, Indonesia can overcome the middle-income trap and achieve long-term economic prosperity.